دراسة خصوبة العيون الشتوية البيولوجية والاقتصادية لصنفي العنب المحليين" شامي أبيض (بلدي)، و "التفاحي" المرباة على عرائش. - مخول جرجس; عطاف وفاء (Latakia University Journal -Biological Sciences Series, 2016)
نُفذ البحث في قرية القلوف في محافظة اللاذقية على شجيرات كرمة للصنفين المحليين "شامي أبيض، و" التفاحي " التابعين للنوع Vitis vinifera L. مرباة على شكل عرائش بعمر10 سنوات مطعمة على الأصلB41، ومزروعة على أبعاد (3×3) م خلال العامين 2013 و2014.وكانت النتائج على الشكل الآتي: - تراوحت خصوبة العيون الشتوية في الصنف شامي أبيض (بلدي) بين 0.11 و 1.37، بوصفهما متوسطاً لعامي الدراسة، كما حققت العين العاشرة على القصبة أعلى خصوبة اقتصادية (1141.25غ)، بوصفها متوسطاً للعامين 2013 و2014، وتفوقت معنوياً على بقية العيون الشتوية. - بينت نتائج الدراسة أن أخصب العيون الشتوية في الصنف المحلي "تفاحي" كانت العين العاشرة أيضاً، وبلغت (1.24)، بوصفها متوسطاً للعامين 2013 و2014، بينما كانت هذه الخصوبة أقلها في العين الأولى (0.33)، وتفوقت العين العاشرة على بقية العيون الشتوية عدا العين التاسعة التي حققت خصوبة قدرها (1.13). وفيما يتعلق بالخصوبة الاقتصادية فقد حققت العين العاشرة، أيضاً، أعلى متوسط وزن للعنقود (2137.75غ)، بوصفه متوسطاً للعامين، تلتها العين التاسعة (1338.05غ)، وتفوقت العين العاشرة معنوياً على بقية العيون الشتوية المدروسة. This research was conducted in Alkallouf village in Lattakia Province on grapevine trees belonging to local varieties Shami Abiad (Local) and Tuffahi in Vitis vinifera L. species grown on 10 years Arbor training grafted on B41 rootstock and planted in 3x3m during 2013 and 2014. And results were as follows: • The best fertility of winter eyes in Tuffahi Local variety were between 0.11 and 1.37 as an average. The tenth eye on a stock has achieved the highest economical fertility (1141.25 g) as a main for 2013 and 2014, and was significantly better than other winter eyes. • The best fertility of winter eyes in Tuffahi Local variety was tenth eye which achieved (1.24) during 2013 and 2014, were fertility was less on first eye (0.33). An eye number ten was significantly better than other winter eyes except an eye number nine which achieved (1.13) fertility. • An eye number ten has achieved the best economical fertility (the main weight of cluster 2137.75 g in two years study) followed by an eye number nine (1338.05 g). An eye number ten was significantly better than other studied winter eyes.